Association between working memory impairment and activities of daily living in post-stroke patients - Fasihah Irfani Fitri; Aida Fithrie; Aldy S Rambe (Medicinski glasnik, 2020)
Aim: Stroke is one of the leading causes of adult disability and functional impairment worldwide. Cognitive impairments including memory dysfunction are common after stroke and may have a negative impact to the functional status and activities of daily living (ADL). The study aimed to determine the impact of working memory impairment after stroke on ADL. Methods: This cross-sectional study involved post-stroke patients who underwent neurologic examination and mini mental state examination (MMSE), forward digit span (FDS) and backward digit span (BDS) to assess cognitive function, and assessment of daily life activities (ADL) and instrumental activities of daily living (IADL) scales. Results: This study included 38 patients, 23 (60.5%) males and 15 (39.5%) females. The mean MMSE, FDS and BDS scores were 24.60±4.49, 4.87±1.166 and 3.47±1.158, respectively. There were 17 (44.7%) patients with cognitive impairment (MMSE Score was lower than 24). The mean ADL and IADL scores were significantly higher in patients with cognitive impairment, showing greater dependency in this group of patients. There was a significant negative correlation between global cognitive function, working memory and ADL and IADL scores in post-stroke patients. Conclusion: Cognitive impairment has a negative impact on daily life activities in post-stroke patients.
Keywords: cognition; function; quality of life; stroke